Development of a real-time simulator for a three-effect falling film evaporator : a thesis presented in partial fulfilment of the requirements for the degree of Master of Technology at Institute of Technology and Engineering, Massey University - Guo, Tong (Massey University, 2003)
The aim of the project was to create a real-time simulator of a falling film evaporator located in the College of Science at Massey University to allow operators to be trained on using the system. This aim was broken into two objectives: the development of a simulink model in Matlab Simulink and secondly the design of control system databases and control screens in Fix32. A specification was initially laid out for these two objectives. A design of the real-time simulator was then made, based around the specifications. The real-time simulator was implemented and then tested to ensure that the initial specifications were met. The final evaporator simulator was an executable file embodying the simulink model controlled by control screens.--Shortened summary.
Keywords: Evaporators; Automatic control; Computer simulation; Process control